Why we should universally cover our mouth and nose in public while battling COVID-19? - Sary Beidas (Archives of Community Medicine and Public Health - Peertechz Publications, 2020)
Most of us are faithfully practicing the 6-foot social distancing rule in public. Some, are even wearing masks while driving alone. On April 3, 2020, the CDC issued voluntary guidelines for the use of cloth face mask (such as a scarf, bandanna or homemade mask) while in public spaces [1,2]. In support of CDC's recommendations for decreasing the transmission rate of COVID-19, we should all strive to wear a cloth face mask (or a standard surgical face mask) when in public when distancing is not feasible. For example, going to the grocery store. Why am I proposing to extend the CDC's voluntary guideline for using a face mask for anyone out in a public space is the subject of this opinion piece?